ICONOSTASIS OF THE CHURCH OF SAINTS PETER AND PAUL THE APOSTLES, IN VRČIN - WORK OF LAZAR AND OLGA KRDŽALIĆ (Heritage, 2023)
The paper analyzes the iconostasis of the Church of the Holy Apostles Peter and Paul, located in Vrčin. The iconostasis was painted in 1896 by Lazar Krdžalić, an artist who studied in Russia for about six years. The artist began his studies at the icon painting school in Moscow, and finished at the Saint Petersburg Academy of Fine Arts. His wife, Olga Krdžalić, helped him paint the iconostasis.The size of the iconostasis partition of the church in Vrčin influenced the iconographic repertoire and the selection of icons with the most prominent saints. The images on the iconostasis are read horizontally, starting from the lower zone and the most important throne icons. In the first and second zones, the most important events from the cycle of major holidays are shown. The Resurrection of Christ is depicted in the central part of the second zone. The icon is larger than other icons, which was intended to highlight the most important event in Christian history. Icons of St. Nicholas and St. John are attached to the scenes from the Great Holidays cycle. The high iconostasis partition ends with a cross on which the Crucifixion is depicted, carrying important symbolic meaning. The crucifixion is completed with the figures of the Virgin Mary, John the Baptist, Michael the Archangel, Saint George, and the scene of the Lamentation of Christ.The iconostasis of the church in Vrčin was painted following Serbian theological practice, heavily influenced by Russia during this period. The application of the iconographic solution that Lazar Krdžalić adopted during his schooling in Russia and its adaptation to the clients indicate that the design of the Vrčin iconostasis follows the practice that was established in the Kingdom of Serbia during the second half of the 19th century.
Keywords: iconostasis, Lazar Krdžalić, Olga Krdžalić, Church of Saints Peter and Paul, Vrčin, church art, 19th century